Death due to Choking in Road Accident: A Case Report - Bhosle, S H; Awasare, R V; Godbole, H V; Dake, M D; Zanjad , N P (Journal of Indian Academy of Forensic Medicine, 2015)
Choking refers to the blockage of internal airways, usually between the pharynx and the bifurcation of the trachea. It is usually due to the inhalation of a foreign body, but it can be caused by inhalation of the products of the disease (or violence) or by anatomical changes due to disease. The choking deaths are mostly accidental and commonly observed in the pediatric age group. Food related items and plastic toys are the foreign materials commonly encountered in choking. The various circumstances reported in the literature when choking occurs were while eating, playing, studying, cleaning ears and making fun. Death due to choking in road accident is very unusual occurrence though road accidents occur frequently. Here we present a case of death due to choking of seven month old boy in road accident resulted due to the unsafe and illegal transportation, ignorance of safety rules, and bad condition of the roads. The joint efforts by personnel of education, engineering, medical, law enforcement agencies are required for prevention of such deaths.